Down-regulation of the cardiac sarcoplasmic reticulum ryanodine channel in severely food-restricted rats - Vizotto, V. A.; Carvalho, R. F.; Sugizaki, M. M.; Lima, A. P.; Aragon, F. F.; Padovani, Carlos Roberto [UNESP]; Castro, A. V. B.; Dal Pai-Silva, M.; Nogueira, Célia Regina [UNESP]; Cicogna, Antonio Carlos [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2007)
We have shown that myocardial dysfunction induced by food restriction is related to calcium handling. Although cardiac function is depressed in food-restricted animals, there is limited information about the molecular mechanisms that lead to this abnormality. The present study evaluated the effects of food restriction on calcium cycling, focusing on sarcoplasmic Ca2+-ATPase (SERCA2), phospholamban (PLB), and ryanodine channel (RYR2) mRNA expressions in rat myocardium. Male Wistar-Kyoto rats, 60 days old, were submitted to ad libitum feeding (control rats) or 50% diet restriction for 90 days. The levels of left ventricle SERCA2, PLB, and RYR2 were measured using semi-quantitative RT-PCR. Body and ventricular weights were reduced in 50% food-restricted animals. RYR2 mRNA was significantly decreased in the left ventricle of the food-restricted group (control = 5.92 +/- 0.48 vs food-restricted group = 4.84 +/- 0.33, P < 0.01). The levels of SERCA2 and PLB mRNA were similar between groups (control = 8.38 +/- 0.44 vs food-restricted group = 7.96 +/- 0.45, and control = 1.52 +/- 0.06 vs food-restricted group = 1.53 +/- 0.10, respectively). Down-regulation of RYR2 mRNA expressions suggests that chronic food restriction promotes abnormalities in sarcoplasmic reticulum Ca2+ release.
Keywords: food restriction; SERCA2; ryanodine channel; phospholamban; mRNA